Hierarchical CBR for Multiple Aircraft Conflict Resolution in Air Traffic Control - Bonzano, Andrea; Cunningham, Padraig (Trinity College Dublin, Department of Computer Science, 1998)
In this paper we present a Case-Based Reasoning system that helps air traffic controllers to solve aircraft conflicts. In particular, we focus on the hierarchical aspect of the CBR system which is able to solve multiple aircraft conflicts, i.e. conflicts that involve three or more aircraft. It is not practical to build a case-base for the different multiple aircraft possibilities as has been done for two aircraft conflicts. Instead we explore the possibility of using case fragments from two aircraft conflicts in multiple aircraft situations. The hierarchical structure that we describe here makes this possible. This involves the use of some high-level analysis of the solutions coming from the case base because the solution to a multiple aircraft conflict is not necessarily one of the solutions of the component two aircraft conflicts. The hierarchical structure allows the use of the same case-base for both two aircraft conflicts and multiple aircraft conflicts with big savings in space and time.
This is a preprint of an article published in Proceedings of 13th European Conference on Artificial Intelligence, ed. Henri Prade, John Wile, pp58-62, August 1998.
Keywords: Computer Science